'I want to stay over': a phenomenographic analysis of a short break/extended stay pilot project for children and young people with Autism. (17th February 2012) - Hallett, Fiona; Armstrong, David
<x xml:space="preserve">Abstract</x> Accessible summary This paper stems from a pilot project offering residential experiences for young people with Autism. The project aimed to offer residential experiences to the young people and help them to develop life skills that would aid their transition to adulthood. The primary purpose of this paper is to analyse the viewpoints of the young people, their parents/carers and the educational and care professionals involved in order to understand the potential impact of projects of this nature. Summary Laying the foundations for an effective transition into independent adulthood is widely perceived as a key priority for practice with children/young people who have Autistic Spectrum Conditions. However, theory and research indicate that, for those children affected, autism often prevents the acquisition, development and expression of key life‐skills which might assist their inclusion in the wider community. In exploring these issues, the authors of this paper report on the Phenomenographic analysis of a Residential Project, involving 16 children per young people who had Autistic Spectrum Conditions, at a Special School in the North West of England. The primary conclusion from this study is that provision for many children and young people with Autistic Spectrum Conditions is most meaningful if it is enabled by practice which: supports the wider human rights and needs of their family; realistically prepares the individual for a life outside of school and the home; and also enriches the unique lifeworld of each young person.